TRANSVERSAL TEACHING PROCESSES WHEN EVALUATING THE CYTOGENETIC EFFECT OF PARANITROPHENOL AND MALATHION IN THE SPECIES Oreochromis sp (RED TILAPIA): THE CASES OF NATURAL SCIENCES AND MATHEMATICS - Carlos Alfredo Sarmiento Arias; Rafael Arturo Fragozo Ruiz; William Antonio Rico Jácome; Marcela Judith Madrid Quintero; Valentina Navarro Salina (International Journal of Medical Toxicology and Legal Medicine, 2024)
This dissertation is part of an academic research that is framed within the requirements of a master’s thesis, as well as an undergraduate monograph, carried out by a group of students and professors linked to the Popular University of Cesar, specifically in the Faculty of Education. The study in question, of greater magnitude, had the fundamental purpose of evaluating the genotoxic effect of paranitrophenol and malathion on the blood cells of the species Oreochromis sp (Red Tilapia), through the implementation of the micronucleus test. Subsequently, this approach was taken up by teachers and students of the Bachelor’s Degree in Mathematics, with the aim of developing transversal teaching processes, based on the case analyzed in the science classes. All of the above was carried out under an experimental design methodology, using the participatory action research model. The main findings of this study revealed, on the one hand, that when evaluating the genotoxic effect, it was determined that paranitrophenol, a highly relevant metabolite of methyl parathion, exhibits a significant genotoxic effect at concentrations of 10, 20 and 40 ng/mL, after a 48-hour exposure period in the species Oreochromis sp. On the other hand, it was evidenced that contextualized teaching, based on fish farming, generates high expectations in students, thus promoting significant learning that transcends the conventional academic environment.